FOXP3+ regulatory T cells as biomarkers in human malignancies. - Bignone, P; Banham, A (2008)
BACKGROUND: Regulatory T cells (Treg) expressing the FOXP3 forkhead transcription factor maintain immunological self-tolerance and can enable tumour cells to escape immunosurveillance. OBJECTIVE: To provide an overview of studies using FOXP3 as a biomarker in human malignancies, particularly in the context of the antibodies used to detect FOXP3 protein expression, the cell populations selected for study, and the detection and scoring methodologies used. METHODS: A personal selection of studies analysing FOXP3 as a marker of Treg cells in human malignancies are discussed. RESULTS/CONCLUSION: FOXP3 is a useful marker that can be used in routine clinical practise to provide both diagnostic and prognostic information in human malignancies. However, the methods and reagents used to detect FOXP3 can have a significant effect on the robustness of experimental findings and conclusions.